2020
DOI: 10.1111/aab.12594
|View full text |Cite
|
Sign up to set email alerts
|

Non‐pesticide alternatives for reducing feeding damage caused by the large pine weevil (Hylobius abietis L.)

Abstract: The large pine weevil (Hylobius abietis L.) is an important pest of young forest stands in Europe. Larvae develop under the bark of freshly cut pine and spruce stumps, but maturing weevils feed on the bark of coniferous seedlings. Such seedlings frequently die because of bark consumption near the root collar. We tested the effect of three treatments (the insecticide alpha cypermethrin, a wax coating and a glue coating) on the feeding damage caused by H. abietis on Douglas fir (Pseudotsuga menziesii) and Norway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(36 citation statements)
references
References 31 publications
0
36
0
Order By: Relevance
“…The significantly higher mortality we recorded in Experiment 2 in western red cedar plants with 0% wax cover, compared to those that were coated seems anomalous. It has been suggested that the white colour of the Kvaae® wax can help to reflect solar radiation and reduce heat injury to seedlings (Lalik et al 2020), but it seems equally likely that our result was simply an artefact of variable quality of the planting stock used. On the three restock sites where we tested it, which all had high populations of Hylobius, wax coating conferred no useful additional benefit when used in conjunction with insecticides, and when applied by itself, compared to acetamiprid, the wax tended to give poorer protection against Hylobius browsing.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The significantly higher mortality we recorded in Experiment 2 in western red cedar plants with 0% wax cover, compared to those that were coated seems anomalous. It has been suggested that the white colour of the Kvaae® wax can help to reflect solar radiation and reduce heat injury to seedlings (Lalik et al 2020), but it seems equally likely that our result was simply an artefact of variable quality of the planting stock used. On the three restock sites where we tested it, which all had high populations of Hylobius, wax coating conferred no useful additional benefit when used in conjunction with insecticides, and when applied by itself, compared to acetamiprid, the wax tended to give poorer protection against Hylobius browsing.…”
Section: Discussionmentioning
confidence: 87%
“…Alternatively "bridging" of brash and other on-site woody detritus may have allowed insects to access and feed on untreated areas of the stem, although Petersson et al (2006) demonstrated that the presence of dead stalks of wavy hair-grass (Deschampsia flexuosa L.) increased browsing damage because it provided a perceived shelter effect from either predators or temperature extremes for the feeding weevils, rather than because it facilitated better physical access to plants. Lalik et al (2020) reported that Kvaae® wax was as efficient as alpha-cypermethrin in successfully preventing Hylobius browsing damage on Norway spruce, but like their insecticide treatment, was not effective in protecting Douglas fir. The somewhat poorer performance of Kvaae® wax treated trees in our work might be because our experiments took place on typical restock sites rather than in controlled conditions which may have led to accelerated breakdown of wax and allowed "bridging" over brash; and because we used different tree species over a longer time period, and at a greater scale.…”
Section: Discussionmentioning
confidence: 99%
“…Shortening of development due to warming climate has recently been recorded in central Europe and emergence of a young generation may occur as early as autumn. Consequently, damage in autumn increases after maturation feeding of young beetles [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…However, some of the above-mentioned species may lack essential nutrients or contain toxic compounds and their consumption reduces damage on conifers and increases weevil mortality [27,31]. From this point of view, establishment of mixed plantings of broad-leaved and coniferous species reduces damages and cost of subsequent protective measures [22,24,29,31].…”
Section: Introductionmentioning
confidence: 99%
“…1 Insecticide-treated seedlings have been commonly used, but for legislation, biodiversity and human health reasons there are ongoing efforts to phase them out. 2 In Sweden and other north European countries, different silvicultural practices as well as stem physical coatings or barriers are used to decrease pine weevil damage and maximize seedling survival. [3][4][5] Yet, these measures cannot be applied at all regeneration sites and vary in efficacy depending on conditions.…”
Section: Introductionmentioning
confidence: 99%